Effects of layer numbers on thermochromic vanadium dioxide coatings - Lim, Shi Ying (Nanyang Technological University, 2021)
Vanadium (IV) oxide or vanadium dioxide (VO2) is the most extensively studied thermochromic material for energy conservation. It changes from transmissive to reflective in the near-infrared (NIR) transmission upon a metal-to-insulator (MIT) phase transition at critical temperature (Tc) of 68°C. However, due to the intrinsic physical properties of VO2, the trade-off between enhancing luminous transmittance (Tlum) and solar modulation ability (ΔTsol) restricts its practical applications. In this research, the purpose is to investigate the effects of layer numbers on thermochromic vanadium dioxide coatings with spacing, from 1-layer to 8-layer. Sample characterisation were done using UV-Vis-NIR spectrophotometer and thermionic scanning electron microscope (SEM). The best result was obtained from 2-layer VO2 thin film, with Tlum of 58.1% and ΔTsol of 9.5%. Further studies such as doping could be done to reduce the critical temperature of VO2 for commercial utilization of VO2 based smart windows.